Oxford handbook of ophthalmology - Denniston, Alastair K. O.; Murray, Philip I. (Oxford University Press, 2014)
This handbook offers a systematic summary of ophthalmic disease directed towards diagnosis, interim assessment and ongoing management. The third edition is an invaluable companion to the practice of ophthalmology, providing rapid access to the information when it is needed, whether in the clinic, theatre or on the ward.